Typification and data on geographic distribution of Scrophularia incisa (Scrophulariaceae) - Sheludyakova, Mariya B. (Phytotaxa, 2022)
Scrophularia incisa Weinmann (1810: 136) (Scrophulariaceae) belongs to section Canina Don (1838: 511). When the species was described, no type specimen was designated, and the species has remained untypified until now. In consequence, a typification is here provided together with an update morphological description and distribution summary prepared based on the examination of herbarium specimens at LE, LECB and MW herbaria.